MEATCHECK: DETEKSI KUALITAS DAGING SAPI BERBASIS MOBILE DEEP LEARNING - Muh. Wildan Mauludy; Goenawan Brotosaputro; Mardi Hardjianto (Universitas Gunadarma, 2025)
Beef is an important foodstuff that affects consumer satisfaction and market value in the meat industry. The purpose of this research is to develop a model to classify beef quality using the transfer learning method. The data collection method is carried out through taking pictures of beef, which are then labeled based on their quality. Classification uses a transfer learning architecture that can improve the performance of the machine learning model generated for the classification of fresh and rotten meat. The model was tested by looking at accuracy, precision, recall, and f1-score. The results showed an accuracy of 61%, precision of 60.78%, recall of 61%, and an f1-score of 60.89%, which was achieved with a learning rate of 0.1, 10 epoch, and batch size of 8. Conclusion, the model developed with the transfer learning algorithm MobileNetV2 was able to classify the quality of beef with a good level of accuracy. The prototype of the developed system can provide real-time predictions, help consumers choose quality meat, and increase market value. Next, it is recommended to increase accuracy and develop models by increasing the size of the dataset and exploring other, more complex architectures.